Economic systems - Grossman, Gregory (New Delhi, 1984)
The positive reception that the first edition of this little book found at universities and colleges in the United States and abroad, has encouraged the author to bring out a more up-to-date version. The revision of the book's content has been prompted by both the rapid change in the factual material pertaining to the various economies, and the lively evolution of the theoretical and conceptual aspects of the broad field that economists now generally call "comparative economic systems." But if-as someone said the problem with history is knowing where to begin, the problem with writing a concise textbook on economic systems is knowing where to stop. The first edition required a very parsimonious handling of topics and empirical examples. Fortunately, the publisher has kindly allotted somewhat more space for the present edition.
Keywords: Economics